Genus Lepisanthes: Unravelling Its Botany, Traditional Uses, Phytochemistry, and Pharmacological Properties - Nadia Mohamed Tarmizi; Syarifah Aisyah Syed Abd Halim; Zubaidah Hasain; Elvy Suhana Mohd Ramli; Mohd Amir Kamaruzzaman (MDPI AG, 2022)
Extensive knowledge related to medicinal characteristics of plants by living in forest or semi-forest habitats and close observations of indigenous communities have led to the discoveries of the genus Lepisanthes and its traditional uses. The genus Lepisanthes is a member of the Sapindaceae family and is found in various regions of the world. Six species of Lepisanthes such as L. alata, L. amoena, L. fruticosa, L. senegalensis, L. rubiginosa, and L. tetraphylla are widely utilized in traditional and folk medicinal systems. They have been used for centuries for the treatment of ailments or symptoms such as pain, dizziness, high fever, frequent passing of watery stool (diarrhea), abscess, and healing of cuts and wounds. Various methodological approaches, mainly in vitro studies, have been employed to further explore the roles of the genus Lepisanthes. The studies identified that the genus Lepisanthes exerts beneficial effects such as antioxidant, antimicrobial, antihyperglycemic, antimalarial, analgesic, and antidiarrheal. However, the summary of the available literature remains inconclusive. This review aims to comprehensively address the botany, traditional uses, phytochemistry, methods, and pharmacological properties of the six commonly used Lepisanthes species. Hence, our review provides a scientific consensus that may be essential in translating the pharmacological properties of the genus Lepisanthes into future novel cost-effective medicines.